ТЕПЛОФІЗИЧНІ ВЛАСТИВОСТІ ПОЛІМЕРНИХ МІКРО- І НАНОКОМПОЗИТІВ ТА ЇХ ЗВ’ЯЗОК ЗІ СТРУКТУРНИМИ ХАРАКТЕРИСТИКАМИ ПОЛІМЕРНОЇ МАТРИЦІ - Fialko, N.; Dinzhos, R.; Sherenkovskyi, Ju.; Prokopov, V.; Meranova, N. (Institute of Engineering Thermophysics of NAS of Ukraine, 2022)
The results of experimental studies of the heat-conducting properties of polymer micro- and nanocomposites based on polyethylene and polycarbonate filled with carbon nanotubes and aluminum particles are presented. The dependences of the heat conductivity of the considered polymer composite materials on the content of the filler are obtained. The possibility of obtaining polymer composites based on polycarbonate with a coefficient of heat conductivity of 50.0 and 25.7 W/(m K) using carbon nanotubes and aluminum particles as fillers, respectively, has been established. The results of studies of the degree of crystallinity of polymer matrices of the considered composites are presented. Data are submitted concerning the correlation between the indicated degree of crystallinity and the heat conductivity coefficient of the studied composite materials. An interpretation of the mechanism of such a dependence is given on the basis of the laws governing the formation of percolation structures from filler particles.